Influence of Corporate Governance, Leverage and Return on Assets (Roa) Against Tax Avoidance in Food And Beverage Companies Listed on The Stock Exchange - Resi Sandy Agraha; Riana Rachmawati Dewi; Endang Masitoh (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aimed to test empirically perngaruh Governace corporate, leverageand return on assets (roa) against tax avoidance on food and beverage companies listed on the Stock Exchange. This analysis uses a variable indpenden audit committee, company size, ownership in institutional, quality audit, leverage and ROA. The population in this study is a food and beverage company listed on the Indonesia Stock Exchange (BEI) in the period 2012-2017. The analytical method used is multiple linear regression analysis. Sampling techniques in this study using purposive sampling, obtained a sample of 66 the number of observations for six years. The results showed that the variables of the audit committee, company size and ROA effect on tax avoidance, while variable kepemilkan institutional, quality audit and leverage no effect on tax avoidance.